Analisis Subtitusi Limbah Lempung Marmer Terhadap Pengaruh Kuat Tekan Mortar - Andi Yusri; Muhammad Syarif; Fauzan Hamdi (Universitas Muslim Indonesia, 2022)
Along with the development of technology and the development of housing and infrastructure development. Therefore, it is also necessary to develop alternative building materials. In this study, it was planned to test the feasibility of marble waste clay as a cement substitution material in the manufacture of mortar. This is one of the solutions for handling industrial waste so that it can be utilized optimally. The purpose of this study was to determine the effect of substitution of marble waste clay on cement, fine aggregate, and water in mortar physically and mechanically. So that it can be seen the possibility of its use in the application of masonry and plastering work. The materials used in this study consisted of Portland Composite Cement (PCC), fine aggregate, water, and marble waste clay as a partial substitute for cement. The tools used in this study have previously been checked for their conditions and capabilities and have been calibrated first. The mortar cube test object was made by inserting fresh mortar mix from a mixing machine with ASTM C 305 standard into a cube mold measuring 5 cm x 5 cm x 5 cm. Testing the compressive strength of mortar after each specimen reached the age of 7, 14, and 28 days. The number of specimens using marble waste clay substitution of 20%, 30%, and 50% as well as normal mortar specimens, each made as many as 9 pieces. All of the specimens were treated with the water curing method. From the results of testing the compressive strength of normal mortar at the age of 28 days obtained a value of 11.91 MPa. While the 20% marble waste clay substitution mortar obtained a compressive strength of 8.73 MPa and the 30% and 50% substitution obtained a compressive strength of 6.66 Mpa and 4.13 MPa, respectively. Based on SNI 6882–2014, it can be assumed that the 20% marble waste clay substitution mortar which reaches 8.73 MPa is greater than the required compressive strength for type N and O mortars which are 5.2 MPa and 2.4 MPa, respectively. So that it is considered to be used as a mortar for wall work, plastering, parapet walls, foundation wall partitions, manholes, canals, road pavements, sidewalks, terraces and other infrastructure works.